Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan Smart Apps Creator pada Materi Perbandingan untuk Siswa Kelas VII UPTD SMP Negeri 5 Kupang - Lagu, Diesnilya; Samo, Damianus Dao; Blegur, Irna Karlina Sensiana (FKIP Universitas Mataram, 2024)
The development of the use of Android-based smartphones among the people of Indonesia is used in various fields, including the field of education. One software that can be used to implement Android-based learning is smart apps creator (SAC). Therefore, this study aims to develop android application-based mathematics learning media on class VII UPTD SMP N 5 Kupang comparison material that is valid, practical, and effective. The method used in this study is the Research and Development (R&D) method using the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The data collection techniques used in this study were interviews, questionnaires, and learning outcomes tests. Data analysis techniques in this study are qualitative data analysis and quantitative data analysis. The results showed that the application met the eligibility criteria that were valid, practical, and effective in the comparison material. The average total validity of learning media by 3 media and material experts is 4.25 so that android application-based mathematics learning media is included in the valid category, subject teacher responses with an average response result of 4.67, responses from small-scale students are 4.7 and large-scale student responses are 4.45 so that android application-based mathematics learning media is included in the practical category, and the percentage of small-scale learning completeness results obtained 80% included in the effective category and large-scale learning completeness results 88.88% so that mathematics learning media based on android applications that have been developed are included in the very effective category.